Ictal electrocardiographic changes in children presenting with seizures - (:unkn) unknown (WILEY, 2012)
Background: The aim of this study was to determine electrocardiographic changes in children during seizures. Methods: We assessed heart rate changes, RR intervals and QT changes during 47 seizures in children. Consecutive QT and RR intervals were measured for 60 s before the seizures, during the seizures and 60 s after the seizures during video electroencephalography monitoring. Results: There were 47 seizures in 18 patients. Five patients had generalized seizures and 13 patients had focal seizures. Twelve patients were male. The mean age during monitoring was 10.1 years (range 4 months-19 years). Ictal tachycardia was seen in every seizure. No ictal bradycardia was noted. There was only one dropped beat in a patient. The mean ictal heart-rate-corrected QT (QTc) interval was significantly higher than the postictal measurements (P = 0.005). Mean ictal QTc variation tended to increase during seizures and then decreased below the pre-ictal measurements in the postictal period. However these changes were statistically insignificant (P > 0.05). RR variance was significantly decreased during seizures compared to the postictal period and the standard deviation of the RR intervals was significantly decreased in the ictal period compared to the pre-ictal period (P = 0.014 and P = 0.001, respectively). Conclusion: Tachycardia is the main finding in seizures in children. Ictal bradycardia and cardiac arrhythmias are very rare despite being more frequent in adults with seizures.
Keywords: children; electrocardiogram; epilepsy; seizure; HEART-RATE-VARIABILITY; SUDDEN UNEXPLAINED DEATH; ECG ABNORMALITIES; CARDIOVASCULAR MORTALITY; UNEXPECTED DEATH; QT DISPERSION; INTERVAL; PROLONGATION; PREDICTION; EEG